2019
DOI: 10.1007/s13197-019-03681-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical adsorption of patulin by Saccharomyces cerevisiae during fermentation

Abstract: Patulin (PAT), a mycotoxin mainly produced by various species of fungi, is frequently detected in moldy fruit-and vegetable-based products, which pose a health risk to the consumer. Over the past decades, a few studies reported that PAT content could be significantly decreased by microbial fermentation process. However, the physical adsorption mechanism between PAT and yeast during fermentation is still unclear. In this paper, we focused on the physical adsorption of PAT by Saccharomyces cerevisiae CCTCC 93161… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Fermentation effectiveness in mycotoxin elimination and reduction has been shown. However, biological control may not be applicable to some foods and feeds [241]. Some researchers have shown that biological detoxification of mycotoxins and its capacity to change their chemical structures is worthy of increased focus [211].…”
Section: Biological Strategiesmentioning
confidence: 99%
“…Fermentation effectiveness in mycotoxin elimination and reduction has been shown. However, biological control may not be applicable to some foods and feeds [241]. Some researchers have shown that biological detoxification of mycotoxins and its capacity to change their chemical structures is worthy of increased focus [211].…”
Section: Biological Strategiesmentioning
confidence: 99%
“…The reduction was statistically significant but much lower than the reduction caused by living cells, especially for C. lusitaniae and R. paludigenum. We assume that the removal of patulin from solution by heat-inactivated cells was caused by adsorption because many microorganisms [ 48 , 49 ], including yeast [ 50 , 51 ], reduce patulin concentration in solution by physical adsorption. The process is likely to be reversible, which further diminishes its attractiveness for applications.…”
Section: Discussionmentioning
confidence: 99%
“…Success in alleviating the effects of ochratoxin A and aflatoxin B1 by utilization of yeast Saccharomyces cerevisiae cell wall in chicken diets has been recently reported by Mendieta et al [ 67 ]. Efficacy of this yeast to remove patulin in fermented foods by physical adsorption has also been proven [ 68 ]. Kluyveromyces marxianus were used to bind aflatoxin B1, ochratoxin A and zearalenone, while authors demonstrated that mycotoxins can be bound especially by the Candida utilis cell [ 69 ].…”
Section: Post-harvest Biological Controlmentioning
confidence: 99%